2018
DOI: 10.3823/2545
|View full text |Cite
|
Sign up to set email alerts
|

Disease Free Survival of Well Differentiated Thyroid Cancer: 20 years Experience at a tertiary care center in Lebanon

Abstract: Background: Thyroid cancer is the most common endocrine malignancy. Although relatively common, to date, there is no study about its prognosis in Lebanon. The objectives of this study were to determine the disease free survival, the recurrence rate and possible predictors of recurrence, as well as the rate of post thyroidectomy complications among patients with differentiated thyroid cancer who received treatment at the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…For Arab and Middle Eastern populations, this study will serve as a reference observation looking at various factors affecting DTC outcomes on long-term follow-up. A female predominance was noted, endorsing similar observations from Egypt, United Arab Emirates, Lebanon, and Yemen [ 22 , 23 , 24 , 25 ]. The average age of onset for thyroid cancer among Arabs was observed to occur during the third decade of life.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…For Arab and Middle Eastern populations, this study will serve as a reference observation looking at various factors affecting DTC outcomes on long-term follow-up. A female predominance was noted, endorsing similar observations from Egypt, United Arab Emirates, Lebanon, and Yemen [ 22 , 23 , 24 , 25 ]. The average age of onset for thyroid cancer among Arabs was observed to occur during the third decade of life.…”
Section: Discussionsupporting
confidence: 83%
“…PTC is the predominant histologic subtype similar to worldwide observations acknowledged in iodine-sufficient regions [ 26 ]. For Arab patients, previous studies that examined the significance of gender on DTC survival were divergent [ 22 , 23 , 24 , 25 ]. In fact, some studies found that gender disparity has no effect on DTC survival at all [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most patients with vascular involvement have N1b disease, with one in every five reported to have distant metastasis, thereby conferring a poorer prognosis. 13 , 35 A retrospective study conducted by Falvo et al, 36 indicated a high rate of lymph node involvement (20.5% vs. 3.8%) and distant metastasis (12.8% vs. 1.66%) in DTC patients with angiovascular invasion compared to those without invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Conflicting reports exist regarding the association between age and gender with disease outcomes in DTC patients. Hajj Boutros et al, 13 noted that age at presentation (i.e., patients < 45 years old) was an important predictor of DFS. Similarly, Jonklaas et al, 14 reported that DTC prognosis was better among females < 45 years of age compared to their age-matched male counterparts.…”
Section: Discussionmentioning
confidence: 99%